015 Temporal trends in head injury outcomes from 2003 to 2010 in England and Wales, and the effect of specialist neurosciences care: a Cohort Study. (14th September 2011) - Fuller, G; Lecky, F; Woodford, M; Bouamra, O; Jenks, T; Coats, T; Hutchinson, P
Abstract : Objectives and Backgrounds: Head injury (HI) is the leading cause of death in trauma, and case fatality rates after blunt HI did not improve in England and Wales between 1994 and 2003. Subsequent national guidelines have recommended that all severe HIs should be treated in neuroscience units (NSUs). The aim of this study was to investigate case fatality trends in HI since 2003 and establish the effect of specialist neuroscience care on mortality after severe HI. Methods: We conducted a cohort study using prospectively recorded data from the TARN trauma registry for adult patients presenting with blunt trauma between 2003 and 2009. Temporal trends in log odds of death adjusted for case mix were examined for patients with and without HI. Rates of transfer and mortality were compared for patients with severe HI treated in NSUs vs non-specialist centres. Propensity score adjusted multivariate logistic regression was then used to calculate case mix adjusted odds of death associated with non-NSU care. Results: Since 2003 there was an average 12% reduction in case mix adjusted log odds of death per annum in patients with HI (n=15 173), with a similar but smaller trend in non-HI trauma mortality (n=48 681). During the study period the proportion of patients with HI treated entirely in non-NSUs decreased from 31% to 19%, (p<0.01). Severe HI management in non-NSUs was associated with a 11% increase in crude mortality (p<0.01) and a case mix adjusted 1.85 (95% CI 1.57 to 2.19) fold increase in odds of death. Conclusions: The reduction in log odds of death following HI since 2003 is consistent with increased levels of treatment in NSUs, or better management following the introduction of national HI guidelines. Our data suggests that increasing transfer rates to NSUs represents an important strategy in further improving outcomes in severe HI.